2021
DOI: 10.3390/epidemiologia2040033
|View full text |Cite
|
Sign up to set email alerts
|

Data-Driven Deep-Learning Algorithm for Asymptomatic COVID-19 Model with Varying Mitigation Measures and Transmission Rate

Abstract: Epidemiological models with constant parameters may not capture satisfactory infection patterns in the presence of pharmaceutical and non-pharmaceutical mitigation measures during a pandemic, since infectiousness is a function of time. In this paper, an Epidemiology-Informed Neural Network algorithm is introduced to learn the time-varying transmission rate for the COVID-19 pandemic in the presence of various mitigation scenarios. There are asymptomatic infectives, mostly unreported, and the proposed algorithm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…The model parameters are summarized in Table 1. Time-varying transmission rates have been shown to efficiently model the spread of COVID-19 [4,11]. Next, will discuss the form of the time-varying transmission rates for each variant.…”
Section: Multi-variant Seir Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The model parameters are summarized in Table 1. Time-varying transmission rates have been shown to efficiently model the spread of COVID-19 [4,11]. Next, will discuss the form of the time-varying transmission rates for each variant.…”
Section: Multi-variant Seir Modelmentioning
confidence: 99%
“…We present a data-driven deep learning algorithm for a model consisting of time-varying transmission rates for each active variant. Using infected daily cases data, we learn the form of the time-varying transmission rates, to reveal a timeline of the impact of mitigation measures on the transmission of COVID-19 [4,5]. It can also be demonstrated that this algorithm shows improvement on short-term forecasting when combined with a recurrent neural network and an adaptive neuro-fuzzy inference system.…”
Section: Introductionmentioning
confidence: 99%
“…Data-driven approaches including neural networks and nonlinear regression have been applied to dynamical systems [7,9,8]. Data-driven approaches are not replacing good intuition and reasoning but instead are unlocking new possibilities [1]. In [12], the authors used Gaussian processes to discover differential equations from data.…”
Section: Preliminarymentioning
confidence: 99%
“…The equilibrium solution of ( 2) is (u e , v e ) as shown in Figure (1). Where the nullclines of the FHN equations are a line and a cubic that intersect in a single rest point.…”
Section: Data Generationmentioning
confidence: 99%
See 1 more Smart Citation